Characteristics of concentration and meditation of elite archers during different training methods - Wei, J.; Wang, L.; Li, L. (Journal of Tianjin University of Sport, 2013)
The purpose of this study is to analysis the effects of concentration and meditation to elite archers` score in their training by the EEG feedback equipment.Methods:12 elite archers trained required or non-required to record score during training,the scores more than 55 in 6 shoots score(excluding 55) was assigned as high score group(HSG),less than 55 (including 55) was assigned as low score group(LSG), and no archery target training as control group(CON), each shooting process EEG data was recorded and analyzed. Result: In the concentration level,the HSG showed no significant different to LSG(P>0.05), but significantly lower than the CON(P<0.05). In the meditation,the HSG was significantly higher than LSG(P<0.01),but no significant was found between HSG and CON. Conclusion: The level of concentration did not significantly affect the performance of archers,high meditation level was much more important for getting better performance and the concentration and meditation level was not contradiction